Corporal Pedagogies: An Introduction - Wendy Ryden (Journal of the Assembly for Expanded Perspectives on Learning, 2018)
Essays in this section address the question: “What happens when we understand teaching and learning as bodily arts that holistically engage us rather than disconnect us from our embodied selves?”